2012
DOI: 10.1167/iovs.12-10371
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Vascular Structures within and Posterior to Sclera in Eyes with Pathologic Myopia by Swept-Source Optical Coherence Tomography

Abstract: Swept-source OCT is a high-quality method to detect intrascleral and retroscleral blood vessels in the eyes with pathologic myopia. These findings and longitudinal studies of these vessels will help in investigating how they are altered in pathologic myopia, and how such alterations are related to the complications in the retina-choroid and optic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 21 publications
(30 reference statements)
1
56
0
Order By: Relevance
“…Previous reports exist in which imaging artifacts were identified in the OCT imaging of sclera [14]. However, the orientation of the features in our imaging and their connection with Haller's layer vessels are inconsistent with the artifacts and suggest vessels, possibly short ciliary arteries or veins of lymphatics [82,87,91]. In general, careful analysis of features present in images of tissue located underneath highly scattering layers is required to avoid erroneous interpretation of artifacts generated by the imaging methods as real structures.…”
Section: Resultsmentioning
confidence: 56%
“…Previous reports exist in which imaging artifacts were identified in the OCT imaging of sclera [14]. However, the orientation of the features in our imaging and their connection with Haller's layer vessels are inconsistent with the artifacts and suggest vessels, possibly short ciliary arteries or veins of lymphatics [82,87,91]. In general, careful analysis of features present in images of tissue located underneath highly scattering layers is required to avoid erroneous interpretation of artifacts generated by the imaging methods as real structures.…”
Section: Resultsmentioning
confidence: 56%
“…As expected, the posterior scleral border was better seen as the AL increased and ST decreased: detection rate increased to 98.5% in eyes with AL > 27.5 mm in our study. Aside from difficulties in visualizing the posterior scleral border, the measurement of ST may be confounded by two other factors: First, the long and short posterior ciliary arteries have been observed within the sclera as linear hyporeflective structures on SSOCT 27 and second, a separation of episcleral fibers from scleral fibers have been observed in highly myopic eyes (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Perforating scleral vessels have been implicated in the pathogenesis of structural changes of the sclera as investigated by OCT and reported by Pedinielli et al 10 and Ohno-Matsui et al 11 More recently, Querques et al 12 reported on the formation of lacquer cracks in pathologic myopia. Assessed by indocyanine green angiography angiography, Moriyama et al 18 found a lower number of PCAs and a displacement of the entry site in highly myopic eyes compared with controls.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple sectorial watershed zones meet in the submacular region, presumably making the macula and the avascular zone of the fovea vulnerable to ischemia under certain conditions. 9 Perforating scleral vessels (PSVs) have been visualized as linear hyporeflective structures at the level of the sclera by EDI-SDOCT and swept-source OCT in pathologic myopia as reported by Pedinielli et al 10 and Ohno-Matsui et al 11 More recently, perforating scleral vessels have been investigated in connection with lacquer cracks in pathologic myopia by Querques et al 12 They have been hypothesized to act as "locus minoris resistentiae," leading to scleral expansion and lacquer crack formation. Because of low signal-to-noise ratio, the visualization of PSVs in emmetropic eyes has been more problematic to date.…”
mentioning
confidence: 88%